PENGARU PENDIDIKAN KESEHATAN DENGAN POSTER TERHADAP PENGETAHUAN REMAJA PUTRI TENTANG PENCEGAHAN KANKER PAYUDARA DI KELURAHAN TUMINTING KAMPUNG TALI KOTA MANADO - Dewi Astuti Sudijanto (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2021)
Breast cancer is the main cause of death among all cancers experienced by women in Indonesia. Breast cancer is one of the health problems throughout the world, the increasing mortality rate due to breast cancer is one of them because it is detected at an advanced stage. Breast cancer prevention efforts can be done by providing health education regarding breast cancer prevention in adolescent girls. The purpose of this research is to determine The effect of health education with posters towards the knowledge of adolescent girls about breast cancer prevention in Tuminting Village, Kamapung Tali, Manado City. The design of this study used the Quasi Experimental method with the Pre-Experimental One Group Pre-test Post-test Design approach. The samples taken for this study were 15 respondents using the Total Sampling method. Data collection using a questionnaire. The results obtained in this study using the McNamer test with ρ value = 0.004 where the value of α < 0.05 which means Ha is accepted. The conclusion of this study is there is an effect of health education with posters towards the knowledge of adolescent girls about breast cancer prevention in Tuminting Village, Kamapung Tali, Manado City.